Lógica matemática no cotidiano escolar - Pinheiro, Marcela Eliane (2020)
Logic and mathematics occupy important positions today, as they are part of our daily lives. Presenting the relevance of these two important themes is the main objective of this work, which addresses the concepts involved with the themes and deals with aspects related to the difficulties and patterns of the application of mathematical logic in daily school life; more specifically, the work aims to provide logic learning for students in the Mathematics subject in elementary school. The paper describes the research that was applied with the students of a school in the peripheral region of the city of São Carlos, a inland city in the state of São Paulo, involving mainly logic issues that were part of the Brazilian Public Schools Mathematics Olympiad.